Influence of Inter Row Spacing and Fertilizer Levels on Seed Production and its Economic Benefits in Perennial Fodder Sorghum cv. CoFS-29 - BAPURAYAGOUDA PATIL; MN MERWADE; LAXMI N TIRLAPUR (Seed Research, 2026)
Maintenance of optimum number of plants per unit area and nutrient management are considered as important management practice for enhancing the seed and fodder productivity in forage crops. Keeping this in view, a field experiment was conducted during kharif 2012 and 2013 at University of Agricultural Sciences, Dharwad to assess the seed yield and economic benefit in perennial fodder sorghum with suitable row spacing and fertilizer levels. The evaluation was conducted with three row spacings (30 cm, 45cm and 60 cm) and four fertilizer levels (100:40:40, 100:60:40, 150:40:40 and 150:60:40 NPK kg ha¹) for two years. The results revealed that 30 cm spacing recorded about 22 per cent more seed yield (657.6 kg ha), 10 per cent more dry fodder yield (126.7 q ha¹) and higher gross returns (Rs. 80967 ha¹), net returns (Rs. 50855 ha¹) and B:C ratio (1.69), as compared to 45 and 60 cm spacings. Among the fertilizer levels, the plants grown at 150:60:40 kg NPK ha¹ have out yielded other doses with more seed yield (641.6 kg ha¹), more dry fodder yield (125.6 q ha¹), increased gross returns (Rs. 79234 ha¹), net returns (Rs.548726 ha¹) and B:C ratio (1.60). From this study, it can be concluded that application of 150:60:40 kg NPK ha¹ with 30 cm row spacing is more economical for seed production of multicut fodder sorghum cv. CoFS-29.